2022
DOI: 10.3389/fimmu.2022.973880
|View full text |Cite
|
Sign up to set email alerts
|

Tas2R signaling enhances mouse neutrophil migration via a ROCK-dependent pathway

Abstract: Type-2 bitter taste receptors (Tas2Rs) are a large family of G protein-coupled receptors that are expressed in the oral cavity and serve to detect substances with bitter tastes in foods and medicines. Recent evidence suggests that Tas2Rs are also expressed extraorally, including in immune cells. However, the role of Tas2Rs in immune cells remains controversial. Here, we demonstrate that Tas2R126, Tas2R135, and Tas2R143 are expressed in mouse neutrophils, but not in other immune cells such as macrophages or T a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Only a few Tas2rs , including Tas2r131 and the Tas2r143/Tas2r135/Tas2r126 cluster, have been tagged genetically in mice (Liu et al, 2017; Voigt et al, 2015). Similarly, only a handful of Tas2r knockout mice involving Tas2r105 and the Tas2r143/Tas2r135/Tas2r126 cluster have been generated in different laboratories (Kobayashi et al, 2022; Lu et al, 2021; Mueller et al, 2005; Perniss et al, 2020). Notably, no cell‐specific knockout mouse has been reported yet.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Only a few Tas2rs , including Tas2r131 and the Tas2r143/Tas2r135/Tas2r126 cluster, have been tagged genetically in mice (Liu et al, 2017; Voigt et al, 2015). Similarly, only a handful of Tas2r knockout mice involving Tas2r105 and the Tas2r143/Tas2r135/Tas2r126 cluster have been generated in different laboratories (Kobayashi et al, 2022; Lu et al, 2021; Mueller et al, 2005; Perniss et al, 2020). Notably, no cell‐specific knockout mouse has been reported yet.…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
“…While qRT-PCR is a reliable and sensitive technique utilized to (Kolodziejczyk et al, 2015) and spatial transcriptomics (Marx, 2021).…”
Section: Challenges and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gram-negative AHLs have been shown to be able to activate other T2Rs than T2R38, including isoforms T2R10 and T2R14 when expressed in HEK93 cells [ 202 ]. In addition to their expression in sinonasal epithelial cells, T2Rs were also identified in immune cells where they may contribute to the detection of quorum sensing molecules [ 203 , 204 , 205 , 206 , 207 , 208 ]. We demonstrated that unprimed macrophages (M0) can be activated by AHLs or quinolones through T2R receptors.…”
Section: Interactions Of T2rs With Pseudomonas Aeruginosa ...mentioning
confidence: 99%
“…However, in macrophages [ 28 ], the transcripts of at least 16 different subtypes (TAS2Rs 3, 4, 5, 7, 8, 9, 10, 14, 19, 20, 31, 38, 39, 43, 45 and 46) have been detected. Both in resident and monocyte-derived macrophages, bitter agonists inhibit cytokine release [ 58 ] and cell migration [ 85 , 86 ] and stimulate reactive species release [ 61 ]. In mast cells, TAS2R3, 4, 10, 14 and 46 are well-expressed and are hypothesized to exert an inhibitory function on leukocytes, particularly by counteracting the release of histamine in IgE-activated cells [ 87 , 88 ].…”
Section: Type 2 Taste Receptors In the Respiratory Systemmentioning
confidence: 99%